2020
DOI: 10.1186/s13023-020-01362-3
|View full text |Cite
|
Sign up to set email alerts
|

ERNICA guidelines for the management of rectosigmoid Hirschsprung’s disease

Abstract: Background: Hirschsprung's disease (HSCR) is a serious congenital bowel disorder with a prevalence of 1/5000. Currently, there is a lack of systematically developed guidelines to assist clinical decision-making regarding diagnostics and management. Aims: This guideline aims to cover the diagnostics and management of rectosigmoid HSCR up to adulthood. It aims to describe the preferred approach of ERNICA, the European Reference Network for rare inherited and congenital digestive disorders. Methods: Recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
124
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 119 publications
(153 reference statements)
1
124
0
2
Order By: Relevance
“…No such study has been reported, but one‐third of Swedish patients with total colonic aganglionosis required additional nutrition and almost one‐quarter were underweight, indicating the presence of underlying malnutrition 2,6 . Recent guidelines for the management of rectosigmoid HD 3 recommend a follow‐up of growth and nutrition, also engaging an interdisciplinary care team comprising gastroenterologists and nutritional therapists. Findings of this study suggest that paediatric nutrition support teams should be aware of parental dietary restrictions in children with HD and, therefore, perform routine nutritional assessments.…”
Section: Discussionmentioning
confidence: 99%
“…No such study has been reported, but one‐third of Swedish patients with total colonic aganglionosis required additional nutrition and almost one‐quarter were underweight, indicating the presence of underlying malnutrition 2,6 . Recent guidelines for the management of rectosigmoid HD 3 recommend a follow‐up of growth and nutrition, also engaging an interdisciplinary care team comprising gastroenterologists and nutritional therapists. Findings of this study suggest that paediatric nutrition support teams should be aware of parental dietary restrictions in children with HD and, therefore, perform routine nutritional assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this aganglionosis, there is a lack of peristaltic movement in the affected bowel with loss of smooth muscle relaxation, resulting in functional constriction. In around 80% of patients, the aganglionic segment is located in the rectosigmoid area, but it may also cover a longer segment, up to the total colon or even the small bowel in rare cases[ 2 - 4 ]. The current method of establishing aganglionosis is by contrast enema, anorectal manometry, and rectal biopsies[ 2 , 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In around 80% of patients, the aganglionic segment is located in the rectosigmoid area, but it may also cover a longer segment, up to the total colon or even the small bowel in rare cases[ 2 - 4 ]. The current method of establishing aganglionosis is by contrast enema, anorectal manometry, and rectal biopsies[ 2 , 4 - 6 ]. Of these options, rectal biopsies are considered to have the highest diagnostic specificity[ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of surgical treatment for HSCR is to remove the aganglionic colon and to anastomose the ganglionic colon above the dentate line (1,5). Transanal endorectal pullthrough (TEPT) is the most current popular procedure in the surgical correction of HSCR since it is less invasive and has many advantages compared with the transabdominal approaches (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%